PENGARUH INDEPENDENSI, SKEPTISME DAN ETIKA PROFESI AUDITOR TERHADAP KUALITAS AUDIT (Studi Empiris Pada KAP DI Kota Malang) - Fatmawati, Aida; Adji, Koenta; Wulandari, Retno (Jurnal Riset Mahasiswa Akuntansi, 2017)
Audit quality is the result of the auditor's performance in carrying out the task in question.Auditors are required to be able to produce high quality audits so that they have a great responsibilitytowards those who have an interest in the financial statements. This study aims to analyze the effect ofindependence, skepticism and professional ethics of auditors on audit quality. The population in this studyare all auditors who work at the Public Accounting Firm in Malang. Sampling was done usingconvenience sampling method, and the number of samples was 60 respondents. This research is a form ofexplanatory research (explanatory research), and the research model is descriptive quantitative, namelydata relating to numbers that still need processing and analysis for research purposes. The method of datacollection is done by distributing questionnaires directly to auditors who work at the Public AccountantOffice in Malang. Data analysis technique used in this study is multiple regression analysis techniques